Pengembangan Media Gambar Seri untuk Meningkatkan Kemampuan Bercerita - Sularti Sularti; Suharno Suharno; Benny Agus Pribadi (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
The purpose of this study was to analyze the use of picture series learning media that was developed in improving storytelling skills in grade I students. This research is a Research and Development (R & D). Data collection techniques with tests, non-tests, and interviews. The effectiveness analysis was carried out by comparing the results of the pretest and posttest tested with the mean difference test (Independent Sample t Test). The results showed that after being validated by media experts and linguists, learning media were suitable to be used to improve storytelling skills. The effectiveness of serial image media as measured using a before-after experimental design in field trials is known to have a pretest value of 69, and an average posttest value of 81.89. Based on the normality test with the One Sample Kolmogorov Smirnov Test, the probability value of t-statistics> Level of Significant = 0.05, namely the pretest value of 0.852 and the posttest value of 0.778 (> 0.05), thus the research data is normally distributed. The results of the t-test obtained a significance value (2-tailed) 0.000 <0.05. Thus, it can be concluded that there is a significant (significant) difference between the pretest and posttest scores in Indonesian language learning, it can be interpreted that serial picture media can improve storytelling skills in grade I KD students. 4.9. Using the right vocabulary and expressions to introduce yourself, your family, and the people in your place of residence in a simple spoken and written form.